Pengembangan Sistem Akuaponik Vertikal untuk Optimalisasi Pemanfaatan Ruang di Perkotaan pada Akuaponik Menggunakan Mikrokontroler Arduino UNO - Ananda Al Buckhori; Tata Sutabri (Router : Jurnal Teknik Informatika dan Terapan, 2024)
Vertical Aquaponics System for Optimal Space Management Overview Due to rapid urban development, less land available for agriculture. Vertical aquaponics systems offer innovative solutions to overcome these problems. This research aims to design and develop a vertical aquaponic system that is efficient and effective in utilizing limited urban space. This system combines fish farming and plant cultivation simultaneously in a closed system. The nutrient-rich water from the fish pond is flowed into the plant substrate in a circular process. The vertical design of the system allows for high productivity in very limited areas. . The results of the study aim to contribute to the development of sustainable urban agriculture and increase food availability in urban areas. Overview Due to rapid urban development, less and less land is available for agricultural activities. Vertical aquaponics systems offer innovative solutions to overcome these problems. This research aims to design and develop a vertical aquaponics system that efficiently and effectively utilizes limited space in the city. This system combines fish farming and plant cultivation simultaneously in a closed system. Nutrient-rich water from fish ponds is flowed into the plant growth substrate. The results of this research are expected to contribute to the development of sustainable urban agriculture and increase food availability in urban areas.